Pengaruh Volume Biogas Reaktor Anaerob Limbah Padi Terhadap Intensitas Cahaya Lampu Petromak - Roswaldi Sk -; Nazris Nazaruddin -; Kartika - - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2017)
The creation of an intelligent biogas reactor made from rice straw is a long-term goal of this research. Biogas reactor is a breeding ground for methanogenesis bacteria in the process of methane gas formation (biogas) which can be used as fuel. The proliferation of these methanogenesis bacteria depends on the temperature, degree of acidity, humidity and volume of raw materials contained in the biogas reactor, if these parameters are out of threshold then the result of methane gas will be reduced or even the methanogenesis bacteria will die will lead to cessation of methane gas production. Increase the biogas gas pressure to be used as fuel of the test object in this case the petromak lamp.